Tax, social policy and gender : rethinking equality and efficiency - Stewart, Miranda, 1968- (ANU Press, 2017)
Gender inequality is profoundly unjust and in clear contradiction to the philosophy of the 'fair go'. In spite of some action by recent governments, Australia has fallen behind in policy and outcomes, even as the G20 group of nations, the Organisation for Economic Co-operation and Development and the International Monetary Fund are paying renewed attention to gender inequality. Tax, Social Policy and Gender presents new research on entrenched gender inequality in a comparative framework of human rights and fiscal sustainability. Ground-breaking empirical studies examine unequal returns to education for women and men, decision-making about child care by fathers and mothers, the history and gendered effects of the income tax and family payments, and women in the top 1 per cent. Contributors demonstrate how Australia's tax, social security, child care, parental leave, education, work and retirement income policies intersect to compound gender inequality. Tax, Social Policy and Gender calls for a rethinking of equality and efficiency in tax and social policy and provides new policy solutions. It offers a pathway to achieve gender mainstreaming for women's economic security and the wellbeing of all Australians.